Pencegahan Tindak Pidana Kejahatan Jalanan Klitih Melalui Hukum Pidana dan Teori Kontrol Sosial - Fuadi Isnawan (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
The number of street crimes involving teenagers and children by the perpetrators requires effective preventive measures. This research aims to analyze the urgency of using criminal law theory and social control to prevent street crime crimes. Data sources are reviewed and analyzed through literature study, and the research method used is normative forensics. This research identifies relevant data sources such as criminal law theory and social control theory that are relevant to the prevention of street crime klitih committed by teenagers. This research identifies data sources related to criminal law theory and social control theory related to criminal behavior in overcoming street crime. The collected data were analyzed to understand the existing legal basis for street crime prevention and to understand the impact of criminal law and social control theory on the prevention of such crimes. The results of this study show that criminal law plays an important role in preventing street crime. Criminal law provisions relating to street crime, including criminal offenses, sanctions and related legal processes, can act as a deterrent and provide protection to the community. Furthermore, social control theory also plays an important role in the prevention of these crimes by involving social institutions, families, schools, and communities in controlling the behavior of adolescents and children.